A Handbook on Community Health Nursing Procedures - Saloma, Pawi (UNIMAS Publisher, 2016)
This book is a step by step instruction on procedures commonly carried out in the maternal and child health clinic settings. It is intended to provide nursing students with a simple yet reliable reference during their clinical placement in the Maternal and Child Health Clinic. The focus of this handbook is on procedures pertaining to antenatal and postnatal care, child health care and family planning. It also covers procedures for vaccine storage, home visit and papsmear taking. Each procedure begins with an overview, the purpose and the requirements needed to perform the procedure.